2014
DOI: 10.4014/jmb.1310.10084
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Citric Acid Production by Wild Yeasts Grown in Glycerol

Abstract: In this study, crude glycerol was used as a carbon source in the cultivation of wild yeasts, aiming for the production of microbial lipids and citric acid. Forty yeasts of different sources were tested concerning their growth in crude and commercial glycerol. Four yeasts (Lidnera saturnus UFLA CES-Y677, Yarrowia lipolytica UFLA CM-Y9.4, Rhodotorula glutinis NCYC 2439, and Cryptococcus curvatus NCYC 476) were then selected owing to their ability to grow in pure (OD600 2.133, 1.633, 2.055, and 2.049, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Other factors that have effects on citric acid production include lipids, such as groundnut oil (Millis et al 1963;Kumar & Ethiraj 1976;Souza et al 2014), and sodium monofluoroacetate (Meixner-Monori et al 1984). Millis et al (1963) showed that lipid will improve the yield of citric acid with no effect of the dry weight of mycelium.…”
Section: Other Factorsmentioning
confidence: 99%
“…Other factors that have effects on citric acid production include lipids, such as groundnut oil (Millis et al 1963;Kumar & Ethiraj 1976;Souza et al 2014), and sodium monofluoroacetate (Meixner-Monori et al 1984). Millis et al (1963) showed that lipid will improve the yield of citric acid with no effect of the dry weight of mycelium.…”
Section: Other Factorsmentioning
confidence: 99%
“…Neste sentido, o glicerol bruto vem sendo estudado como fonte de carbono para o crescimento de biomassa microbiana, produção de biodiesel e outros compostos como o ácido cítrico (Souza et al, 2014;Yen et al, 2015). Porém, o glicerol bruto apresenta possíveis inibidores do crescimento, como traças dos reagentes e do catalisador do processo de biodiesel (metanol e KOH), o que tem produzido inconvenientes, com rendimentos menores de crescimento celular, comparado ao glicerol purificado (Silva, Mack & Contiero, 2009).…”
Section: Discussionunclassified
“…A raiz deste, vários estudos foram desenvolvidos diante da possibilidade de usar o glicerol bruto como fonte de carbono de leveduras oleaginosas (leveduras com mais de 20% de lipídios na massa seca) para crescimento de biomassa microbiana (Raimondi et al, 2014;Yen et al, 2015) e produção de ácido cítrico e lipídios (Souza et al, 2014;Yen et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The main fatt y acid in the yeast biomass was oleic acid (C18:1n9; 38.2 %), as observed when using other oleaginous yeasts (31,32). Oleic acid was described as the main monounsaturated fatt y (36). In turn, using industrial fats in the process with yeast resulted in a different total fatt y acid composition, which was characterised by a high concentration of cellular stearic acid (37).…”
Section: The Nutritional Value Of Y Lipolytica Mk1 Biomassmentioning
confidence: 99%